Analisis Pengelolaan Piutang Negara di Masa Pandemi Covid-19 pada Direktorat Jenderal Kekayaan Negara (DJKN) Sumatera Utara - Rahmi Pamela Putri; Saparuddin Siregar (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This study aims to analyze or test how the state receivables management system works during the Covid-19 pandemic at DJKN North Sumatera. This research uses a type of descriptive qualitative research and secondary data served as the research user’s data source. This research was obtained in a library study, this is the result of research collected by researchers from various sources according to the needs of research data on the management of state receivables during the Covid-19 pandemic at the Directorate General of State Assets in Medan. Based on the research results, it can be concluded that, as we know, during the pandemic there were challenges for agencies everywhere, including the DJKN North Sumatera. One of these challenges is that some debtors experience problems in paying their debts due to the impact of Covid-19. The existence of assistance from the government's efforts through the Crash Program is a solution and an opportunity for fresh air for debtors, this effort is in accordance with the DJKN's vision and mission which is to become a professional and accountable manager of state assets for the prosperity of the people.